1997
DOI: 10.1021/js960405a
|View full text |Cite
|
Sign up to set email alerts
|

Gentamicin-Loaded Hydraulic Calcium Phosphate Bone Cement as Antibiotic Delivery System

Abstract: A hydraulic calcium phosphate cement made of beta-tricalcium phosphate [beta-Ca3(PO4)2], monocalcium phosphate monohydrate [Ca(H2PO4)2-H2O], and water was used as a delivery system for the antibiotic gentamicin sulfate (GS). GS, added as powder or as aqueous solution, was very beneficial to the physicochemical properties of the cement. The setting time increased from 2 to 4.5 min with 3% (w/w) GS and then slowly decreased to 3.75 min with 16% (w/w) GS. The tensile strength increased from 0.4 to 1.6 MPa with 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
103
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(121 citation statements)
references
References 23 publications
17
103
1
Order By: Relevance
“…[38] where a β-TCP/phosphoric cement was investigated, a similar temperature dependence for the formation of brushite or monetite was reported; at 37°C the main phase after reaction was brushite and at 55°C the main phase was monetite. Furthermore, studies have reported dehydration of brushite, forming monetite, at 37°C in PBS [15,39,40]. In the present study it was shown that brushite, in fact, can be formed also in the premixed system, but only at lower temperatures than in the water mixed system.…”
Section: Citationsupporting
confidence: 59%
“…[38] where a β-TCP/phosphoric cement was investigated, a similar temperature dependence for the formation of brushite or monetite was reported; at 37°C the main phase after reaction was brushite and at 55°C the main phase was monetite. Furthermore, studies have reported dehydration of brushite, forming monetite, at 37°C in PBS [15,39,40]. In the present study it was shown that brushite, in fact, can be formed also in the premixed system, but only at lower temperatures than in the water mixed system.…”
Section: Citationsupporting
confidence: 59%
“…Since the microstructure of cast and injected samples without gentamicin was not obviously different it may be assumed that the positive influence of residual β-TCP dominates the effect of porosity changes for these samples. Interestingly, Bohner et al noted an improvement in tensile strength of brushite cements as a result of gentamicin addition [36]. This was ascribed to the decrease in size and thickness of DCPD particles due to the presence of sulphate ions in gentamicin (35 ± 2%).…”
Section: 1mentioning
confidence: 99%
“…Moreover, in several studies [18][19][20][21][22] the conditions used were not indicated. Hence, most studies in the literature disregard the fact that the release pattern may change depending on the time the cement was set for; only Canal et al compared the drug release patterns of cements set for different times (1 h vs 7 days), but this was done on apatitic cements only [10].…”
Section: Introductionmentioning
confidence: 99%